Evaluation of a User Guidance Reminder to Improve the Quality of Electronic Prescription Messages - Dhavle, A.A.; Corley, S.T.; Rupp, M.T.; Ruiz, J.; Smith, J.; Gill, R.; Sow, M. (Applied Clinical Informatics, 2014)
Background: Prescribers’ inappropriate use of the free-text Notes field in new electronic prescriptions can create confusion and workflow disruptions at receiving pharmacies that often necessitates contact with prescribers for clarification. The inclusion of inappropriate patient direction (Sig) information in the Notes field is particularly problematic.Objective: We evaluated the effect of a targeted watermark, an embedded overlay, reminder statement in the Notes field of an EHR-based e-prescribing application on the incidence of inappropriate patient directions (Sig) in the Notes field.Methods: E-prescriptions issued by the same exact cohort of 97 prescribers were collected over three time periods: baseline, three months after implementation of the reminder, and 15 months post implementation. Three certified and experienced pharmacy technicians independently reviewed all e-prescriptions for inappropriate Sig-related information in the Notes field. A physician reviewer served as the final adjudicator for e-prescriptions where the three reviewers could not reach a consensus. ANOVA and post hoc Tukey HSD tests were performed on group comparisons where statistical significance was evaluated at p<0.05Results: The incidence of inappropriate Sig-related information in the Notes field decreased from a baseline of 2.8% to 1.8% three months post-implementation and remained stable after 15 months. In addition, prescribers’ use of the Notes decreased by 22% after 3 months and had stabilized at 18.7% below baseline after 15 months.Conclusion: Insertion of a targeted watermark reminder statement in the Notes field of an e-prescribing application significantly reduced the incidence of inappropriate Sig-related information in Notes and decreased prescribers’ use of this field.Citation: Dhavle AA, Corley ST, Rupp MT, Ruiz J, Smith J, Gill R, Sow M. Evaluation of a user guidance reminder to improve the quality of electronic prescription messages. Appl Clin Inf 2014; 5: 699–707http://dx.doi.org/10.4338/ACI-2014-03-CR-0022
Keywords: Electronic prescribing; errors; electronic transmission of prescriptions; quality improvement; computerized physician order entry system